2013
DOI: 10.1128/mcb.01597-12
|View full text |Cite
|
Sign up to set email alerts
|

ATM Mediates pRB Function To Control DNMT1 Protein Stability and DNA Methylation

Abstract: eThe retinoblastoma tumor suppressor gene (RB) product has been implicated in epigenetic control of gene expression owing to its ability to physically bind to many chromatin modifiers. However, the biological and clinical significance of this activity was not well elucidated. To address this, we performed genetic and epigenetic analyses in an Rb-deficient mouse thyroid C cell tumor model. Here we report that the genetic interaction of Rb and ATM regulates DNMT1 protein stability and hence controls the DNA meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…Interestingly, p300 has also been shown to bind directly to the LXCXE domain of HPV16 E7 (Bernat et al, 2003), providing a potential direct link between the Rb binding site of E7 and the regulation of NBS1 stability. Furthermore, previous studies have linked Rb inactivation to ATM activation and DSB induction (Pickering and Kowalik, 2006; Shamma et al, 2013, 2009), as well as the control of Tip60-dependent acetylation of ATM (Shamma et al, 2013), which is required for ATM autophosphorylation and activation. Importantly, recent studies have shown that Tip60 is required for productive replication of HPV31 (Hong et al, 2015b), presumably through facilitating ATM activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, p300 has also been shown to bind directly to the LXCXE domain of HPV16 E7 (Bernat et al, 2003), providing a potential direct link between the Rb binding site of E7 and the regulation of NBS1 stability. Furthermore, previous studies have linked Rb inactivation to ATM activation and DSB induction (Pickering and Kowalik, 2006; Shamma et al, 2013, 2009), as well as the control of Tip60-dependent acetylation of ATM (Shamma et al, 2013), which is required for ATM autophosphorylation and activation. Importantly, recent studies have shown that Tip60 is required for productive replication of HPV31 (Hong et al, 2015b), presumably through facilitating ATM activation.…”
Section: Discussionmentioning
confidence: 99%
“…High-risk E7 expression has been shown to lead to DSB induction and genomic instability in a manner thought to be dependent on Rb inactivation and deregulation of E2F transcription factors (Bester et al, 2011; Duensing and Munger, 2002; Pickering and Kowalik, 2006). Inactivation of Rb outside the context of HPV infection is sufficient to induce DSBs, formation of γH2AX and MRE11 positive foci, and increase levels of ATM, Chk2, and Chk1 (Frame et al, 2006; Pickering and Kowalik, 2006; Shamma et al, 2013, 2009). Previous studies demonstrated that expression of high-risk HPV31 E7 alone is sufficient to induce ATM signaling (Moody and Laimins, 2009), raising the possibility that E7 contributes to the differentiation-dependent phase of the life cycle through modulation of the DDR.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, TP53 polymorphism has shown modulator function in DNA methylation of carcinoma [7]. ATM is another gene mediating DNA methylation [8]. ATM inactivating mutant had been shown its resistant to those DNA damaging drugs probably through the immune system, which affected efficacy of chemotherapy to leukemia [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, determining the functions of RB in these contexts is challenging because of complicated cellular response to the loss of function of RB . For example, the germline loss of Rb results in increased intracellular signaling, DNA damage responses, and cellular senescence ; this generated technical difficulties in addressing RB functions especially in controlling undifferentiated state.…”
Section: Introductionmentioning
confidence: 99%